2001
DOI: 10.1086/319523
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a Novel Gene (IMMP2L) by a Breakpoint in 7q31 Associated with Tourette Syndrome

Abstract: Gilles de la Tourette syndrome (GTS) is a complex neuropsychiatric disorder characterized by multiple motor and phonic tics. We identified a male patient with GTS and other anomalies. It was determined that he carried a de novo duplication of the long arm of chromosome 7 [46,XY,dup(7)(q22.1-q31.1)]. Further molecular analysis revealed that the duplication was inverted. The distal chromosomal breakpoint occurred between the two genetic markers D7S515 and D7S522, which define a region previously shown to be disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 26 publications
(28 reference statements)
0
121
0
4
Order By: Relevance
“…7 On the other hand, we could amplify the entire NM_001244606.1 transcript and we showed that this transcript had two 5 0 non-coding exons of 54 and 74 bp (designated exon 1a and 1b, respectively). Throughout the text we use NM_001244606.1 as the long IMMP2L transcript.…”
Section: Other Alternative Transcripts Of Immp2lmentioning
confidence: 98%
See 3 more Smart Citations
“…7 On the other hand, we could amplify the entire NM_001244606.1 transcript and we showed that this transcript had two 5 0 non-coding exons of 54 and 74 bp (designated exon 1a and 1b, respectively). Throughout the text we use NM_001244606.1 as the long IMMP2L transcript.…”
Section: Other Alternative Transcripts Of Immp2lmentioning
confidence: 98%
“…6 In 2001, a boy with a de novo inverted duplication, dup(7)(pter-q31.1::q31.1-q22.1::q31.1-qter), presenting with vocal and motor tics was reported. 7,8 The 7q31 breakpoint was within the region described by Boghosian-Sell and colleagues 6 and disrupted a novel gene, IMMP2L. 7 These two studies implicated 7q31 as a candidate TS region.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further studies identified that a novel gene, IMMP2L (MIM 605977), was interrupted by both the breakpoint in the duplicated fragment and the insertion site in 7q31. 7 We describe the detailed molecular genetic analysis of an 18-yearold boy with a de novo translocation t(2;7)(p24.2;q31) who developed motor tics at the age of 13 years and has significant speech and language impairment. The breakpoints are further characterised and the IMMP2L gene is found to be disrupted and partially deleted by the translocation, along with a cryptic 7.2-Mb deletion involving a number of genes.…”
Section: Gilles De La Tourette Syndrome (Gts (Mim 137580)mentioning
confidence: 99%